THE BEST STORIES IN THE BEST ORDER? CANONS, APOCRYPHAS AND (POST)MODERN READING - Cunningham, Valentine (Literature and theology, 2000)
Bible reading occurs at intersection of perpetually shifting canons—of textual meaning, interpretative strategies, and preferred textual menu for particular contemporary consumption. Such continual up-to-datedness is the Bible's, as it is the classic's, only survival kit. Contemporary reading is the only reading—ever Post-modernism's biblical reading menu is notable for its post-modernist yields of meaning, but textual post-modernism—aporias textual unboundedness, canonical on-edgedness, apocryphalism, etcetera—is typical of biblical texts' ur-post-modernism (the Bible living up, of course, to applied post-modernist reading expectations). All such reading is an aestheticisation a fictionalising process—abusive naturally, constructively abusive, perhaps, but always catachretical, demythologising, a negative theology. But, of course, this is utterly inevitable for now.